Answer:
[tex]y = -\frac{4}{3}x+ 4[/tex]
Explanation:
Given
[tex](x_1,y_1)=(-3,8)[/tex]
[tex](x_2,y_2)=(0,4)[/tex]
Required
Determine the line equation
First, calculate the slope (m)
[tex]m = \frac{y_2 - y_1}{x_2 - x_1}[/tex]
This gives:
[tex]m = \frac{4-8}{0 - (-3)}[/tex]
[tex]m = \frac{4-8}{0 +3}[/tex]
[tex]m = \frac{-4}{3}[/tex]
[tex]m = -\frac{4}{3}[/tex]
The equation is then calculated using:
[tex]y = m(x - x_2) + y_2[/tex]
Where
[tex]m = -\frac{4}{3}[/tex] and [tex](x_2,y_2)=(0,4)[/tex]
So, we have:
[tex]y = -\frac{4}{3}(x-0) + 4[/tex]
[tex]y = -\frac{4}{3}x+0 + 4[/tex]
[tex]y = -\frac{4}{3}x+ 4[/tex]